A Compact-Type CIP Method for General Korteweg-de Vries Equation. (3rd August 2014) - Shi, YuFeng; XU, Biao; Guo, Yan
Abstract : We proposed a hybrid compact-CIP scheme to solve the Korteweg-de Vries equation. The algorithm is based on classical constrained interpolation profile (CIP) method, which is coupled with high-order compact scheme for the third derivatives in Korteweg-de Vries equation. Several numerical examples are presented to confirm the high resolution of the proposed scheme.